Porphyrin and phthalocyanine photosensitizers designed for targeted photodynamic therapy of colorectal cancer. (15th January 2021) - Janas, Katarzyna; Boniewska-Bernacka, Ewa; Dyrda, Gabriela; Słota, Rudolf
Graphical abstract: Abstract: Colorectal cancer is of particular concern due to its high mortality rate count. Recent investigations on targeted phototherapy involving novel photosensitizers and drug-delivery systems have provided promising results and realistic prospects for a successful medical treatment. New research trends have been focused particularly on development of advanced molecular systems offering effective photoactive species which could be selectively delivered directly into the affected cells. Porphyrins and phthalocyanines have been considered extremely attractive for this purpose due to their molecular versatility, excellent photochemical properties and multifunctional nature. In this review it has been demonstrated that such macrocyclic compounds may effectively contribute to the inhibition of the growth of colon cancer cells and eventually to their photonecrosis. Purposely designed and tailored porphyrin and phthalocyanine derivatives in combination with smart drug-carriers have proved suitable for photodynamic therapy (PDT) and related antitumor treatments. This survey comprises a choice of potentially applicable ideas developed since 2010 involving 9 different tumor cell lines and featuring 32 photosensitizers.